Descriptive body composition profile in female Olympic volleyball medalists defined using multichannel bioimpedance measurement: Rio 2016 team case study - Bankovic, V.; Dopaj, M.; Terzic, Z.; Nesic, G. (International Journal of Morphology, 2018)
The subject of this paper was the study of the morphological status of top elite women volleyball players, Rio 2016 Olympic medal winners, with the aim of obtaining reliable quantitative data, used to determine the morphological model and to control the morphological status of top elite women volleyball players. This study tested 12 top elite women volleyball players who participated in the 2016 Rio Olympic Games and won the silver medal. Measurements of body composition were conducted one day before departing for the Rio Olympic Games, on 25th June, 2016, using electrical bioimpendance analysis (BIA), with the InBody 720 Tetrapolar 8-Point Tactile Electrode System analyzer. The study included 29 variables: 17 original variables, four voluminosity-dependent variables, six longitudinality-dependent variables, and two combined index variables. The results showed that average height of the women players was 188.93±6.49 cm, the overall mean BM value for the Serbian team was 75.56±6.97, the overall mean BMI value for the team was 21.08±1.30 kg•m-2, while the mean values for percent skeletal muscles and body mass were 48.95±1.78 % and 13.43±2.70 %, respectively. Upon a thorough analysis of the results of the study, it can be argued that in all measured anthropomorphological characteristics the top elite women volleyball players from the tested sample had a body type of remarkable basic longitudinality, i.e., BH, and a body composition mainly characterized by very high muscle mass but such a low amount of body fat that it bordered on the biological minimum for women